Geochemistry and petrology of Palaeocene coals from Spitsbergen — Part 1: oil potential and depositional environment - Marshall, Chris; Large, David J.; Meredith, Will; Snape, Colin E.; Uguna, Clement N.; Spiro, Baruch F.; Orheim, Alv; Jochmann, Malte; Mokogwu, Ikechukwu; Wang, Yukun; Friis, Bjarki (Elsevier, 2015)
Abundant oil prone coal (Type III kerogen) deposits are preserved within the high latitude, middle Palaeocene, Todalen member of the Central Tertiary Basin, Spitsbergen Island, Norwegian Arctic. The coals (Svea, Longyear, Svarteper and Askeladden seams) have been subjected to only minor previous geochemical characterisation. Focussing upon the Longyear seam, this paper characterises the present, prospective and economic oil potential of the Svalbard coals. Organic biomarker parameters, Fe–S chemistry and coal maceral analysis are then applied to understand the provenance and environmental origins of this unusual source rock. The upper Todalen Mbr. coals (Longyear, Svarteper and Askeladden seams) have significantly more oil potential than the Lower Svea seams with estimated retortion yields of 170–190 kg/tonne vs. 24 kg/tonne respectively. The Longyear seam exhibits relatively high HI values (ca. 300–400 mg/g TOC) consistent with a hydrogen rich mixed Type II/III kerogen source. Greatest oil potential is shown to be favoured by formation within a fen environment, with high bacterial degradation (> 100 μg/g TOC hopanes), marine influence (> 0.5 wt.% sulfur, Fe/S < 0.9) and the unique temperate high latitude Palaeocene climate of Svalbard leading to preservation of hydrogen rich organic matter via organo-sulfur bond formation.